PENGARUH STRES DALAM PEKERJAAN TERHADAP KINERJA KARYAWAN: STUDI KASUS DI PERUSAHAAN AGRIBISNIS PT NIC - Arif Imam Suroso; Rotua Siahaan (School of Business, Bogor Agricultural University (SB-IPB), 2006)
This study was aimed at finding out the existence of stress in work towards employees’ performance, and knowing the indicators of each shaper element of that influencing the employees’ performance of plant department of agribusiness industry at PT. NIC. The method of this study is case study involving 155 respondents. Using the Structural Equation Modelling (SEM), it is known that the influence of stress in work towards employees’ performance is significantly negative. It means that the advance of stress in work can take the employees’ performance down. The advance of stress in work was stimulated by stressor, in this case are job pressure and lack of support. The relationship between stressor and stress in work is positively significant. Lack of support is the most influence indicator of stressor variable instead of job pressure. This study concludes that stress in work significantly influence the employees’ performance. Generally, stress in work at plant department of PT. NIC is in low category (41.9%) and the performance is in high/good category (60.6%). It means that the existence of stress in work at this time have positive characteristics because it has played the role as motivator to work.